The effect of biogas slurry and inorganic fertilizer on soil fertility and yield of cucumber (Cucumis sativus L.) - Wiwin Sumiya Dwi Yamika; Ninuk Herlina; Sherly Amriyanti (Brawijaya University, 2019)
Combining the application of organic manure with inorganic fertilizer treatment can improve the productivity of the cucumber. Biogas slurry is synthesized from organic manure that can improve soil fertility and increase the yield of cucumber. This research aimed to learn the effect of biogas slurry and inorganic fertilizer on soil fertility and its impact on yield of cucumber and to learn the role of biogas slurry in decreasing amount of inorganic fertilizer used on the crop. This research was conducted in former paddy field located in Wriginsongo village, District of Tumpang, Malang Regency from March to May 2017. A randomized block design factorial was used with biogas slurry treatment as the main plot which consists of three levels: 10 t ha-1, 20 t ha-1, and 30 t ha-1while the subplot was the dosages of inorganic fertilizer which consists of100%,75%and 50% dosage of recommendation. This research revealed that biogas slurry treatment could increase the organic matter on the plant. There were some interactions between biogas slurry and inorganic fertilizer in the number of fruits produced, the weight of the fruit, the total weight of fruit produced per plant and hectare. Biogas slurry improved organic matter from 0.29% to 2.06%, N total from 0.06% to 0.15%, P2O5 from 93.48 ppm to 224.31 ppm, K2O from 2.01me 100 g-1 to 100 me 100 g-1, and C/N ratio from 3 to 9.